Orchid Inventory and the Host in Meru Betiri National Park â€“ East Java - DWI MURTI PUSPITANINGTYAS (Biodiversitas Journal of Biological Diversity, 2007)
Meru Betiri National Park is located in southern part of East Java Province. Inventory of orchid species was conducted to study orchid diversity in Meru Betiri National Park, especially in Bandealit coastal area. Observation of orchid within host trees was also done to study the preference host trees for orchid growth. It was recorded that there were 25 orchid species belonging to 20 genera. Twenty species of which are epiphyte and 5 species are terrestrial. The most common epiphyte orchids were Pomatocalpa latifolia, Pomatocalpa spicata, Rhynchostylis retusa, Micropera pallida and Grosourdya appendiculata. While terrestrial orchid was only found in a small number, with common terrestrial orchids were Corymborkis veratrifolia and Goodyera rubicunda. The most preference host trees for epiphyte orchid were Tectona grandis (Teak), Clausena indica, Lagerstroemia speciosa, Mangifera indica (Mango), but there is no specific relationshipbetween host trees and epiphyte orchidÂ© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: orchid, host trees, Meru Betiri National Park